A Summation of Fibonacci Numbers

Level 2

The "Fib function" , F ( n ) F(n) , returns the corresponding Fibonacci number :

F ( 0 ) = 0 F(0) = 0 , F ( 1 ) = 1 F(1) = 1 , F ( 2 ) = 1 F(2) = 1 , F ( 3 ) = 2 F(3) = 2 , F ( 4 ) = 3 F(4) = 3 , F ( 5 ) = 5 F(5) = 5 , F ( 6 ) = 8 F(6) = 8 , F ( 7 ) = 13 F(7) = 13 , F ( 8 ) = 21 F(8) = 21 , ... and so on.

The "SumFib function" , S ( n ) S(n) , returns the corresponding cumulative sum of Fibonacci numbers:

S ( 0 ) = 0 S(0) = 0 , S ( 1 ) = 1 S(1) = 1 , S ( 2 ) = 2 S(2) = 2 , S ( 3 ) = 4 S(3) = 4 , S ( 4 ) = 7 S(4) = 7 , S ( 5 ) = 12 S(5) = 12 , S ( 6 ) = 20 S(6) = 20 , S ( 7 ) = 33 S(7) = 33 , S ( 8 ) = 54 S(8) = 54 , ... and so on.

Question : Aside from the first three distinct values of each function, { 0 , 1 , 2 0, 1, 2 }, are there any other shared values (or outputs) of both of these functions?

It is not currently known No Yes

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tj Evert
Sep 26, 2018

If we advance the recursive relation for Fibonacci numbers , F ( n ) = F ( n 2 ) + F ( n 1 ) F(n) = F(n-2) + F(n-1) , by 2 places, we get F ( n + 2 ) = F ( n + 1 ) + F ( n ) F(n+2) = F(n+1) + F(n) .

Rearranging these terms gives us a modified recursive relation, F ( n ) = F ( n + 2 ) F ( n + 1 ) F(n) = F(n+2) - F(n+1) .

Summing these: (Note: I've written F ( n ) F(n) as F ( n 0 ) F(n-0) to simplify the formatting)

F ( n 0 ) = F ( n + 2 ) F ( n + 1 ) F(n-0) = F(n+2) - \underline{F(n+1)}

+

F ( n 1 ) = F ( n + 1 ) F ( n 0 ) F(n-1) = \overline{F(n+1)} - \underline{F(n-0)}

+

F ( n 1 ) = F ( n 0 ) F ( n 1 ) F(n-1) = \overline{F(n-0)} - \underline{F(n-1)}

+

F ( n 1 ) = F ( n 1 ) F ( n 2 ) F(n-1) = \overline{F(n-1)} - \underline{F(n-2)}

+

.

.

.

+

F ( 0 ) = F ( 2 ) F ( 1 ) F(0) = \overline{F(2)} - F(1)

_ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ (notice that the "over-lined" terms cancel out the underlined terms)

S ( n ) = F ( n + 2 ) 1 S(n) = F(n+2) - 1

.

Since S ( n ) = F ( n + 2 ) 1 S(n) = F(n+2) - 1 , then for all n > 2 n > 2 , the summation S ( n ) S(n) can't equal a Fibonacci number.

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...